"Dressed in an Angel's Nightshirt": Jesus and the BBC. (13th January 2017) - Veldman, Meredith
Abstract: This article examines images of Jesus broadcast on the BBC from the 1930s through the 1950s. During these years, the BBC sought to use its cultural influence to replace popular religiosity with what the clerics who staffed its Religious Broadcasting Department (RBD) regarded as a more masculine, modern, and vigorous national religious faith. To achieve this aim, the RBD marshaled the might of British New Testament scholarship and its image of a warrior-like, apocalyptic historical Jesus. Yet the RBD's hopes of bridging the gap between popular religiosity and its own vision of Christianity went unrealized. Programs on Jesus that reached a genuinely national audience— The Man Born to be King, Dorothy L. Sayers's wartime radio drama, and Jesus of Nazareth, a popular television series from the 1950s—instead featured Anglicized and ahistorical images deeply embedded within British popular culture. The story of Jesus on the BBC highlights both this popular culture's strength and Christian Britain's fragmentation.